Liposuction - Park, Jin Yong (Springer Singapore, 2018)
This book provides easy-to-understand descriptions of high-quality liposuction techniques applicable to different parts of the body, including the face, abdomen, breasts, arms, buttocks, thighs, and calves. The coverage also encompasses the liposuction treatment of osmidrosis and fat injection techniques (facial, breast, and stem cell). Drawing on his extensive experience of more than ten thousand cases of liposuction and fat and stem cell transplantation, the author presents important new theoretical perspectives and novel surgical approaches that he has personally developed. These include the MDMP technique (multi-direction, multi-position), which is straightforward to perform and offers significant benefits. All procedures are described step by step, from preparation through to completion. The book is superbly illustrated throughout, with a wealth of informative photographs that will aid the practitioner. It will be of high value for experienced plastic and cosmetic surgeons and also for residents and fellows.